Fatigue life monitoring program of RMAF MiG-29 / Wahyu Kuntjoro ... [et al.] - Kuntjoro, Wahyu; Bahari, Ibrahim; Ujang, Abdul Ghani; M Mydin, Assanah (Research Management Institute (RMI), 2008)
The Royal Malaysian Airforce (RMAF) operates one squadron of MiG-29 which were designed on Safe Life principle. RMAF conducts a fatigue life monitoring program to these airplanes. This activity is conducted based on the experience of having the fatigue life monitoring program to the RMAF F/A-18D. The fatigue life of RMAF MiG-29 is based on the wing-fuselage lug joint structure, and Low Cycle Fatigue (LCF) approach is adopted. The stress spectra of this component, is derived through mapping of g-spectra to the 1-g stress level of the lug. The g-history is obtained from the accelerator installed in the airplane, while the 1-g stress level is obtained by finite element modeling of the wing structure and lug joints. Rainflow cycle counting procedure was then applied. The fatigue characteristics (strain-life) of the lug material was obtained from the laboratory test, using the lug material sample, combined with the empirical formula of strain-life diagram. Notched effect is taken into account using Neuber theory. Mean stress effect is dealt with using Smith-Watson-Topper formula. Miner's rule is used to calculate the fatigue damage accumulation. A fatigue life prediction software for RMAF MiG-29 which incorporates the above concepts had been developed. Currently, this software is operational with the RMAF MiG-29, and is being used as part of its Aircraft Structural Integrity Program (ASIP). This paper reports on the development of the fatigue life monitoring strategy and software for the RMAF MiG-29.